Evaluation of Shear Dilation Capability/Potential and Permeability Changes in Karamay Oil Sands under Water Injection - Yanfang Gao; Huiwen Pang; Yan Jin; Mian Chen (Geofluids)
Water injection can effectively improve the reservoir porosity and permeability by shear dilation in the vicinity of wellbores. In this paper, shear dilation and permeability improvement capability/potential are proposed to describe the evolutions of porosity and permeability under water injection-induced shear. The mathematical models based on Karamay oil sand microstructures derived from ESEM (environmental scanning electron microscope) are established to predict the shear dilation effects based on the particle packing theory. Triaxial compression and permeability experiments are conducted to validate the theoretical models, and the experimental data is consistent with model results. Also, the study compares shear dilation capabilities evaluated from three scales: ESEM (μm), laboratory triaxial compression tests (cm), and field injection tests (m). Major conclusions through an application on the wellpair A-2 in area A of the Karamay oil field showed that the oil sands have an excellent shear dilation potential. The larger arrangement angle results in stronger shear dilation and permeability, which means a lower arrangement angle provides a higher potential for improvement. The shear dilation capabilities predicted by ESEM, triaxial compression experiments, and field injection data descend in turn, which indicates that the actual shear dilation capability is difficult to be utilized by present field operations.